DEVELOPMENT OF CREATIVE ACTIVITY AND PROFESSIONAL COMPETENCE OF YOUTH IN EDUCATION - Kholboyeva Nilufar; Masharipova Gularam Kamilovna (Journals Park Publishing, 2024)
This article provides information about the relevance of teaching natural sciences, the formation of students' natural-scientific literacy based on the practice of bilingualism in teaching biology, pedagogical experiments based on the CLIL method and their results.
Keywords: Bilingualism, CLIL, knowledge, skills, competence, integration, innovation, coherence, consistency, experience-testing.